2005
DOI: 10.1111/j.1399-3038.2005.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic urticaria and associated coeliac disease in children: A case–control study

Abstract: The presence of CD in children with CU was significantly more frequent than in controls. GFD resulted in urticaria remission. CD may be regarded in such subjects as a cause of CU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 19 publications
3
65
0
2
Order By: Relevance
“…Caminiti et al (26) reported four patients with Hashimoto thyroiditis out of 95 patients with chronic urticaria, similar to our results. Brunetti et al (23) found no autoimmune diseases in any of 93 patients with chronic urticaria.…”
Section: Discussionsupporting
confidence: 83%
“…Caminiti et al (26) reported four patients with Hashimoto thyroiditis out of 95 patients with chronic urticaria, similar to our results. Brunetti et al (23) found no autoimmune diseases in any of 93 patients with chronic urticaria.…”
Section: Discussionsupporting
confidence: 83%
“…In a study by Caminiti et al (28) conducted in Italy, 9 out of 95 (9.5%) children with chronic urticaria had anti-thyroid autoantibodies, 4 of them with Hashimoto's disease. In contrast, Brunetti et al (20) reported that none of the 93 studied children with chronic urticaria, also recruited from Italy, showed signs of thyroid autoimmunity.…”
Section: Thyroid Autoimmunitymentioning
confidence: 98%
“…There are case reports of an association between chronic urticaria and coeliac disease, which may improve on a gluten-free diet [105,106].…”
Section: Aetiology and Mechanismsmentioning
confidence: 99%